The Soweto stroke questionnaire - L. A. Hale; C. J. Eales; V. U. Fritz (AOSIS, 1998)
A questionnaire was designed for a recent survey into the outcome of stroke patients in Soweto, named the Soweto Stroke Questionnaire (SSQ). It was based on the Barthel ADL Index (BI) but modified to suit the local context. This paper introduces the SSQ, and reports on its inter-rater reliability and its concurrent validity. Fifty-four subjects, in the age range 30 to 75 years, were interviewed and nineteen re-interviewed using the SSQ. Four different scores were calculated: a total score, a Barthel Index score, an Impairment score, and a Quality of Life score. The Pearson's Correlation Coefficient was found to be high between the total score and the BI score. (r=0.948) which supports the concurrent validity of the developed questionnaire. In assessing the reliability of the SQQ, the Wilcoxin Test showed that there was no significant difference between the initial and repeat interviews for the total score, the Barthel Index score, and the Impairment score (p<0,05). The Quality of Life Score came closer to a difference, but not statistically significantly so. These tests were collaborated by Bland and Altman graphs which showed that in 95% of the time, the questions were repeatable. Mc Nemar's Test of Symmetry showed that 34 out of 38 questions asked were found to have over 70% correlation. Four questions showed a lower correlation, the lowest being 63.16%. The SSQ was found to have interrater reliability, and to be concurrently valid to the Barthel Index. It is quick and easy to use, requiring no sophisticated equipment or training. It still requires to be investigated for sensitivity and predictiveness, and to be validated in a more general South African stroke population.